A pathogenic variant in the SETBP1 hotspot results in a forme‐fruste Schinzel–Giedion syndrome. Issue 8 (22nd May 2020) - Sullivan, Jennifer A.; Stong, Nicholas; Baugh, Evan H.; McDonald, Marie T.; Takeuchi, Akihito; Shashi, Vandana
Abstract: Schinzel–Giedion syndrome (SGS; OMIM 269150) is an ultra‐rare genetic disorder associated with a distinctive facial gestalt, congenital malformations, severe intellectual disability, and a progressive neurological course. The prognosis for SGS is poor, with survival beyond the first decade rare. Germline, de novo heterozygous variants in the SETBP1 gene cause SGS with the pathogenic variants associated with the SGS phenotype missense and confined to exon 4 of the gene, clustered in a four amino acid (12 bp) hotspot in the SKI homologous region of the SETBP1 protein. We report a patient with a de novo I871S variant within the SKI homologous region, which has been associated with the severe phenotype previously; but our patient has fewer features of SGS and a milder course. This is the first report of a forme‐fruste phenotype in a patient with a pathogenic variant within the SGS hotspot on the SETBP1 gene and it highlights the importance of considering atypical clinical presentations in the context of severe ultra‐rare genetic disorders.